Comparative Study of Heat Transfer Rate in Solar Water Heater by Varying the Sun Incoming Angle and Flow Rate of Sun Heat Absorpting Fluid - Joni Rahmadi; Fuazen; Indra Lukman (PT FORMOSA CENDEKIA GLOBAL, 2023)
The issue of Green Energy, which is about clean and environmentally friendly energy, is a very important issue at this time. Energy that has the above properties is renewable energy. Optimization of energy absorption needs to be done and this is usually done by conditioning or manipulating several parameters so that the energy absorption rate is more effective and efficient.Therefore, the authors conducted a study that is expected to know at the angle of arrival and the rate of flow what is the most optimal absorption of heat from solar energy for the installation and seeding of Solar Water Heater in Pontianak City. And it is expected that with this research can be a recommendation of energy absorption rate, especially those who use solar energy for the Pontianak City area of West Kalimantan to be optimal and efficient.Based on the results of research and analysis conducted in this study for the setting of the sun's coming angle of 450 and coolant fluid flow rate setting, namely the Solar Collector Loop side of 1250 ccm and on the Domestic Heater Water Loop of 1000 ccm in solar water heater. The setting of angles and flow rate settings in the conditions mentioned are very suitable for the condition of Pontianak city area which provides a very stable efficiency value and the value is close to 100% and the value of heat transfer is quite optimal both the absorption of solar heat and heat absorption by heated water